Islamic Values in TikTok’s Digital Da’wah and Their Implications for Islamic Education Learning - Fitria Wahud; Yuni Maimuna; Karmila Alamsyah Wellem (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
The development of digital da'wah through social media has been widely studied, but studies specifically mapping Islamic values ​​in TikTok da'wah content and its relevance to Islamic Education learning are still limited and tend to be descriptive. This study aims to analyze the Islamic values ​​contained in digital da'wah on TikTok, including aspects of faith, sharia, and morals, also examine their implications for Islamic Education learning in schools and universities. This study uses a qualitative approach through literature review, by thematically analyzing various journal articles, books, and previous research results discussing digital da'wah, media literacy, and Islamic education. The analysis results show that da'wah content on TikTok consistently represents faith values ​​through strengthening monotheism, sharia values ​​through habituating worship and muamalah practices, also moral values ​​through internalizing religious attitudes in daily life. These findings confirm that integrating TikTok-based digital da'wah into Islamic Education learning has the potential to strengthen Islamic digital literacy, increase student engagement, and provide more contextual and relevant learning to the characteristics of the digital generation. This research contributes to the development of a digital media-based PAI learning approach that is adaptive to the challenges of the technological era.